Mining tailings effects from Mariana dam disaster in Minas Gerais, Brazil, on germination, biometric parameters, mineral content, photosynthetic metabolism, morphoanatomy and mycorrhizal colonization in Brachiaria decumbens Stapf. (Poaceae) - Silva, Daniel Rodrigues da (2020)
After more than four years, the country still remembers what was one of the worst socio- environmental disasters in history. The catastrophic Fundão dam rupture in Mariana - MG, southeastern Brazil, which occurred in November 2015, launched more than 50 million cubic meters of iron mining tailings Technosols (IMTT) into the environment. The tailings quickly followed the drainage of Gualaxo do Norte, Carmo and Rio Doce rivers in Minas Gerais, arriving at the mouth of Rio Doce in Atlantic Ocean, leaving a trail of destruction along the way. This IMTT "tsunami" caused death of people, destruction of villages and urban infrastructure, displacement of hundreds of families, riparian forest suppression, impact on water bodies, among others. Currently, in the pastures affected by IMTT, the species Brachiaria decumbens Stapf. (Poaceae) is one of the most common plants, therefore, the work objective was to evaluate the effects of IMTT released in Rio Doce basin on ecophysiology, morphoanatomy and mycorrhizal colonization in B. decumbens, in addition, we seek to test the effects on affected soil quality when mixing the IMTT launched in Rio Doce basin with the soil unaffected by IMTT. For this, the unaffected soil by IMTT (Ref), the Technosol with a thick deposition of iron mining tailings (Tec) was sampled in Barra Longa - MG and we made a mixture of 50 % of each soil type (Ref/Tec) for a greenhouse experiment that lasted for 110 days, cultivating B. decumbens in these three soil types. Our results showed that the iron mining tailings Technosols (Tec) are poor in nutrients, particularly in zinc and organic matter and caused iron toxicity which resulted in decrease in growth, development, mineral content and photosynthetic metabolism of B. decumbens. Corroborating previous studies, it was observed in IMTT a poor nutritional status. The Ref/Tec soil for having superior quality to Tec proved to be an suitable approach for use in areas where Technosols of iron mining tailings were deposited, representing an important step for a quick recovery of these soils, for agricultural, pasture production and for environmental restoration. Keywords: Rio Doce. Forage grass. Nutritional deficit.